Entre documentos e memórias: gestão do patrimônio documental da Universidade Católica de Pernambuco. - Belian, Lucia Freire (2023)
The Institutional Memory discussed here is made up of collective records, evidence of the existence of a social group. Among these records, administrative documents that are produced for functional purposes and that are part of this institutional memory stand out. Safeguarding these documents through document management is essential for the preservation of this memory, as historical research also benefits from it. Organizing and making these documentary sets available is essential for access by historians and researchers in general. With a focus on the Higher Administration Archive of the Catholic University of Pernambuco, this report adopted action research, associated with exploratory type documents, with a qualitative analysis approach and aimed to analyze how the management of documentary heritage is constituted as a means for the preservation of Institutional Memory and History. As research results, I present the manual Between Documents and Memories: Management of Documentary Heritage of the Catholic University of Pernambuco, detailing the document management plan applied to the aforementioned archive; two articles published, one based on the trajectory of UNICAP and the other on Institutional documents as a historical source; the organization of the catalog and authorship of a chapter in the Catalog of Photographic Collections of the Catholic University of Pernambuco: 80 years of history and memories and the Photographic Exhibition commemorating 80 years of UNICAP. This work brought a new discussion about the use of administrative documents as a primary source, when available, for the writing of history. In addition to contributing to the efficiency of recovery and preservation of documentary heritage and archiving in general.